Comparing ADA and IDF diagnostic criteria for intermediate hyperglycaemia and diabetes in the SHiDS study - Zhang, Yinan; Liu, Shuang; Cao, Baige; Xu, Jinfang; Jia, Weiping; Wang, Congrong (Diabetes research and clinical practice, 2025)
This study aimed to assess the prevalence of IH and diabetes, as well as insulin secretion, insulin sensitivity, and related curve patterns in subjects with different glucose tolerance categories according to the diagnostic criteria established by the American Diabetes Association (ADA) and the more recently published International Diabetes Federation (IDF) guidelines. We used data of 5,387 adult participants from the Shanghai High-risk Diabetic Screen (SHiDS) study. All participants underwent a five-point 75 g oral glucose tolerance test (OGTT). Glycemic states were then classified according to the ADA/IDF diagnostic criteria, while OGTT-derived indices were employed to evaluate insulin secretion and sensitivity. Overall, 3,729 subjects were diagnosed consistently under ADA/IDF criteria; while 941 and 717 subjects exhibited inconsistencies in the diagnostic classification for diabetes and IH, respectively. Notably, all of these individuals with discrepant diagnoses displayed β-cell dysfunction and/or insulin resistance compared to the NGT/NGT group. The ADA criteria can identify individuals with elevated haemoglobinA1c (HbA1c) levels when the 1-hour plasma glucose (1-h PG) stay within the normal range, while the IDF criteria can identify subjects with impaired insulin sensitivity and secretion when fasting plasma glucose (FPG), 2-hour plasma glucose (2-h PG) and HbA1c values are in the normal range.